A process for detecting benzo[a]pyrene in polluted aquatic environments - Varnamkhasti, Ali Karami; Christianus, Annie; Shamsuddin, Zulkifli; Ishak, Zamri; Syed, Mohd. Arif (2011)
The present invention relates to a process for detecting benzo[a]pyrene (BaP) in polluted aquatic environments. The process comprising: preparing a plurality of treated fish; retaining some of the plurality of treated fish for a certain period as a control group; exposing rest of the plurality of treated fish for a certain period to a BaP-polluted environment; extracting materials from intestine of the plurality of treated fish; plating materials extracted from the previous step on Cetrimide Agar; and counting Pseudomonas aeruginosa colonies. The population of P. aeruginosa in the fish intestine is used in determining levels of pollutants especially BaP levels in aquatic environments.